Apoios em dente de vigas de concreto leve armado e protendido - Silva, Augusto Cláudio Paiva e (1974)
Tests on twenty half-joints (tooth-shaped end of a beam) of ten ligthtweight concrete beams were carried out. Five were reinforced concrete beams and five prestressed concrete beams. Five different joint reinforcement details were tested. The joints were reinforced so that reinforcement yielding failures and failures by crushing of the concrete strut could be studied. The prestress influence on the half-joint behavior was studied and tests showed that it is not important. A comparison of the half-joint stiffness for the different reinforcement details is shown. Studies on the methods of calculating the ultimate bearing reaction are presented. Many tests resulted in bond failures of the beam tensile reinforcement. Reinforcement procedures are suggested.